Pharmacokinetic parameters and mechanism of action of an efficient anti-Aβ single chain antibody fragment - Esquerda-Canals, Gisela (PLoS One, 2019)
The success of the targeting of amyloid-β (Aβ) oligomers through immunotherapy in Alzheimer’s disease (AD) mouse models has not been translated into the clinics. The use of single-chain variable fragments (scFvs) has been proposed to prevent the potential severe effects of full-length mAbs by precluding crystallizable fraction-mediated microglia activation. The efficacy of scFv-h3D6, a bapineuzumab-derived anti-Aβ scFv, has been extensively proven. In this work, we compared scFv-h3D6-EL, an elongated variant of the scFv-h3D6, with its original version to assess whether its characteristic higher thermodynamic stability improved its pharmacokinetic parameters. Although scFv-h3D6-EL had a longer half-life than its original version, its absorption from the peritoneal cavity into the systemic compartment was lower than that of the original version. Moreover, we attempted to determine the mechanism underlying the protective effect of scFv-h3D6. We found that scFv-h3D6 showed compartmental distribution and more interestingly crossed the blood–brain barrier. In the brain, scFv-h3D6 was engulfed by glial cells or internalized by Aβ peptide-containing neurons in the early phase post-injection, and was colocalized with the Aβ peptide almost exclusively in glial cells in the late phase post-injection. Aβ peptide levels in the brain decreased simultaneously with an increase in scFv-h3D6 levels. This observation in addition to the increased tumor necrosis factor-α levels in the late phase post-injection suggested that the engulfment of Aβ peptide/scFv-h3D6 complex extruded from large neurons by phagocytic cells was the mechanism underlying Aβ peptide withdrawal. The mechanism of action of scFv-h3D6 demonstrates the effectivity of Aβ-immunotherapy and lays the background for other studies focused on the finding of a treatment for AD.